Pathogenic potentials and shedding probability of Salmonella enterica serotype Kentucky in experimentally infected backyard chicken - Najmin, Shamima; Qayum, MD Omar; Biswas, Paritosh Kumar; Das, Shubhagata; Nath, Babu Kanti (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Salmonella is a widely-reported zoonotic bacterial pathogen and human infection is mostly attributed through direct or indirect contact with chickens. Salmonella Kentucky (S. Kentucky) is one of the motile serovars which has recently been identified from both poultry and human samples in Bangladesh. This study was conducted to assess its pathogenic potentials and shedding probability in backyard chicken. Materials and methods: We infected 22 backyard chickens orally, each with 106 cfu of Salmonella Kentuckey, which were then observed for 23 days to enlist clinical signs, gross and histo-pathological changes. Polymerase chain reaction (PCR) for Salmonella was applied on some representative samples to identify the presence of Salmonella. Results: Four chickens were sacrificed and the internal organs were examined to observe gross and microscopic tissue changes. Some reactive changes were seen in spleen during prolonged course of infection. The probability of S. Kentucky shedding was 77% (95%; CI 54-90%) on DPI 2, 41% (95%; CI 21-60%) on DPI 12 and 13% (95%; CI 3-31%) on DPI 21. The survival probability of the infected chickens was 50% (95%; CI 28-68%) on DPI 6, 32% (95%; CI 14-51%) on DPI 15 and 14% (95%; CI 3-31%) on DPI 23. Conclusion: Zoonotic S. Kentucky strain of human non-typhoidal clinical cases of gastroenteritis has potentials to produce clinical signs such as reduced feed uptake, watery or pasty fecal droppings and lesions, such as catarrhal enteritis and typhlitis. http://doi.org/10.5455/javar.2018.e268